Analisis ikhtilaf dalam penggunaan produk perbankan syariah di bank muamalah : studi terhadap perbedaan pandangan ulama pada produk murabahah, mudharabah, dan musyarakah - Ummah, Fina Zaimatul (Maliki Interdisciplinary Journal, 2026)
This article examines the differences of opinion regarding the use of Islamic banking products at Bank Muamalah, focusing on fundamental principles such as the prohibition of riba, gharar, and maysir. The key products analyzed include murabahah, mudarabah, and musyarakah, with debates surrounding their compliance with Islamic principles. There are varying opinions among scholars, particularly regarding murabahah, which some consider akin to riba, as well as challenges related to profit and risk sharing in mudarabah and musyarakah. Additionally, differing implementations of fatwas by banks can confuse customers, potentially undermining public trust. This article emphasizes the importance of transparency from banks and collaboration among relevant institutions to create products that better align with Islamic principles.